Justice-Oriented Learning: Reconfiguring Experiential Education with a California Farmworker Community - Munter, Judith Hope; Harkleroad, Nathan; Cervantes, Manuel; Tinajero , Andrea (Experiential Learning and Teaching in Higher Education, 2022)
None provided